﻿The Trap That Skilled Negotiators Miss - Wadhwa, Monica; Savani, Krishna (MIT Sloan Management Review, 2026)
In negotiations, first offers act as powerful psychological anchors — and even skilled negotiators struggle to escape them. New research published in the Journal of Experimental Social Psychology finds that adopting a choice mindset when you receive a first offer can reduce anchoring: The simple act of reminding yourself that you can choose any counteroffer expands the range of options you consider, helping you negotiate on your own terms.